Penjualan Bayi oleh Ibu Kandung dalam Perspektif Hukum Pidana - Triana, Ramadhani; Sari, Diana Lukita; Zulfiani, Anita (Indonesian Journal of Social Sciences and Humanities, 2026)
The sale of babies by biological mothers is a form of human trafficking that violates the law, humanitarian values, and children's rights. This phenomenon demonstrates a shift in the family's role from protector to exploiter of children. This study aims to analyze the legal regulations regarding baby selling from the perspective of human trafficking and the forms of criminal liability imposed on biological mothers as perpetrators. The research method used is normative legal research with a statutory and case-based approach. Primary and secondary legal materials were analyzed qualitatively and normatively. The results indicate that the act of baby selling fulfills the elements of a crime as stipulated in Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking and Law Number 35 of 2014 concerning Child Protection. In Decision Number 328/Pid.Sus/2023/PN Pal, the judge applied the idealist concursus theory because a single act violates more than one criminal provision. The biological mother, as the perpetrator, can be held criminally responsible if she meets the elements of capacity to take responsibility and culpability. Strict law enforcement and preventive measures are needed to prevent the recurrence of similar crimes.